2020
DOI: 10.1097/rti.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Burnout Among Cardiothoracic Radiologists

Abstract: Purpose: Burnout is a psychological syndrome in response to chronic occupational stressors. The prevalence of burnout among medical professionals has been increasing, and recent studies have shown that radiologists are among those affected. We investigated the prevalence of burnout and assessed associated factors among cardiothoracic radiologists. Materials and Methods: Society of Thoracic Radiology members were invited to complete an anonymous cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Within radiology, studies of subspecialty cohorts of radiologists have consistently demonstrated a high prevalence of radiologist burnout. These include musculoskeletal radiologists [10], neuroradiologists [11], pediatric radiologists [12], breast radiologists [13], and cardiothoracic radiologists [14]. These surveys are potentially prone to response bias.…”
Section: Myth 1-burnout Does Not Existmentioning
confidence: 99%
“…Within radiology, studies of subspecialty cohorts of radiologists have consistently demonstrated a high prevalence of radiologist burnout. These include musculoskeletal radiologists [10], neuroradiologists [11], pediatric radiologists [12], breast radiologists [13], and cardiothoracic radiologists [14]. These surveys are potentially prone to response bias.…”
Section: Myth 1-burnout Does Not Existmentioning
confidence: 99%
“…An electronic survey was sent to the entire membership of the STR, a voluntary professional society of practicing cardiothoracic radiologists. 6 Two separate email messages were sent to the email addresses on file for each member, separated by 10 days. The survey was closed 7 days after the second email.…”
Section: Population and Samplementioning
confidence: 99%
“…The thresholds for emotional exhaustion, depersonalization, and perceived low personal accomplishment were MBI subscale scores of 27 or higher, 10 or higher, and 33 or lower, respectively. 6 Statistical analysis was performed using Excel (Microsoft, Redmond, WA), the open-source statistical computing packages pandas 9 and SciPy 10 for Python, and Jupyter Notebook, 11 an open-source interactive computing platform.…”
Section: Analysis and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous survey of burnout among members of the Society of Thoracic Radiology (STR), 4,5 85.6% of respondents reported the presence of 1 or more of the 3 components of burnout: emotional exhaustion (EE); depersonalization (D); and low personal accomplishment (LPA). Burnout was reported by 84.3% of cardiothoracic radiologists in academic practice and 92.5% of those in private practice and in 84.1% of men and 88.1% of women.…”
mentioning
confidence: 99%